1938
DOI: 10.1037/h0062931
|View full text |Cite
|
Sign up to set email alerts
|

The major determinants of the prediction of social events.

Abstract: I. THE PROBLEMM ODERN psychological literature reveals no systematic empirical analysis of the factors that influence the predictive judgment. Yet predictions, like any other form of psychological response, are lawfully determined. It is of obvious practical and theoretical importance for psychologists to discover the nature of the major determinants of prediction, and the laws of their operation. The study to be reported in the following pages represents an initial attack upon this problem.Predictions are ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

1965
1965
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(27 citation statements)
references
References 18 publications
0
27
0
Order By: Relevance
“…If the aim is prediction, forecast or projections, different approaches are available based on formal modelling, trend extrapolations, probabilistic approaches and expert opinions [28][29][30][31][32][33][34][35][36]. Guessing what the future may bring was not the primary scope of this study and as a result we did not take this direction.…”
Section: Analysis: Interpreting Our Results Within Common Narratives mentioning
confidence: 99%
See 1 more Smart Citation
“…If the aim is prediction, forecast or projections, different approaches are available based on formal modelling, trend extrapolations, probabilistic approaches and expert opinions [28][29][30][31][32][33][34][35][36]. Guessing what the future may bring was not the primary scope of this study and as a result we did not take this direction.…”
Section: Analysis: Interpreting Our Results Within Common Narratives mentioning
confidence: 99%
“…A discussion on how propensities at an individual level can affect participation in Future Studies is also found in [45]. For a different literature, anticipating the future is a defining feature of life and a crucial component of human cognitive abilities [33,[46][47][48][49][50]. In all these studies, the focus is on the individual and to a lesser extent on communities and social contexts.…”
Section: Analysis: Interpreting Our Results Within Common Narratives mentioning
confidence: 99%
“…As a final test of desirability bias we moved from investigating the impact of desirability to the impact of ambiguity, a necessary condition for motivated construal (Kunda, 1990;Marks, 1951;McGregor, 1938). We used the absolute value of the point spread as a measure of the ambiguity of evidence about the game's outcome, (Buckley & Sniezek, 1992).…”
Section: Optimism and Desirabilitymentioning
confidence: 99%
“…In the assessment of social attitudes the role of autism has long been appreciated (cf. Campbell, 1950;Cattell & Baggaley, 1956;Cronbach & ravis, 1944;McGregor, 1938); there is every reason to suppose that it plays a part in selfdescription as well.…”
Section: Social Desirabilitymentioning
confidence: 99%